Burns & Trauma - Wu, Jun
Burns & Trauma is an open access, peer-reviewed journal publishing the latest developments in basic, clinical and translational research related to burns and traumatic injuries. With a special focus on prevention efforts, clinical treatment and basic research in developing countries, the journal welcomes submissions in various aspects of biomaterials, tissue engineering, stem cells, critical care, immunobiology, skin transplantation, prevention and regeneration of burns and trauma injury.